2009
DOI: 10.1111/j.1399-5448.2008.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous subcutaneous insulin infusion vs. multiple daily injections in children with type 1 diabetes: a systematic review and meta-analysis of randomized control trials

Abstract: Original ArticleContinuous subcutaneous insulin infusion vs. multiple daily injections in children with type 1 diabetes: a systematic review and meta-analysis of randomized control trialsPań kowska E, B1azik M, Dziechciarz P, Szypowska A, Szajewska H. Continuous subcutaneous insulin infusion vs. multiple daily injections in children with type 1 diabetes: a systematic review and meta-analysis of randomized control trials. Pediatric Diabetes 2009: 10: 52-58.Objective: To investigate potential effects of continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
134
1
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(162 citation statements)
references
References 25 publications
13
134
1
14
Order By: Relevance
“…It should be considered that subgroup analysis failed to detect any relevant improvement of metabolic control with CSII in younger children, even if this result is controversial [27]. The reasons for the apparent lack of superiority in children are speculative; it can be hypothesized that young children are unable to perform accurate adjustments of prandial insulin doses, or that they are less likely to administer additional boluses in case of moderate hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that subgroup analysis failed to detect any relevant improvement of metabolic control with CSII in younger children, even if this result is controversial [27]. The reasons for the apparent lack of superiority in children are speculative; it can be hypothesized that young children are unable to perform accurate adjustments of prandial insulin doses, or that they are less likely to administer additional boluses in case of moderate hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…In our meta-analysis, we included only trials with a similar method of insulin administration in both control and experimental groups. Previous meta-analyses had already shown that CSII compared with MDI was a more effective form of metabolic control (20,21). Therefore, assessment of the efficacy of RT-CGM is not possible if the insulin delivery method is different in experimental and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Over 80% of patients included in our analysis were treated with CSII. Our previous meta-analysis demonstrated a statistical difference between CSII and MDI therapies (20). CSII therapy was associated with a significant reduction in HbA1c in comparison to MDI, without an increased risk of major hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Several metaanalyses show a statistical difference in favour of pump therapy, but only amounting to a minimal improvement of 0.2 -0.3% in HbA1c values. [9][10][11][12] Similarly, continuous subcutaneous glucose sensing devices exist to improve blood glucose control, but again by a clinically unimportant amount. [13] It is gratifying that every one of our patients had access to a refrigerator.…”
Section: Discussionmentioning
confidence: 99%